Asymptomatic abdominal wall and incisional hernias: Is therapeutic decision consensual? An international survey. (December 2020) - Jaquet, Romain; Darnis, Benjamin; Bonnot, Pierre Emmanuel; Mohkam, Kayvan; Passot, Guillaume; ,
Abstract: Introduction: Hernia pathology is one of the leading causes of surgery worldwide. For asymptomatic patients, surgery remains questionable. The objective of this study was to evaluate the practices of a large population of digestive surgeons with asymptomatic hernia. Methods: Between October 2016 and March 2017, French-speaking digestive surgeons were invited to respond to an online survey consisting of 13 common clinical situations concerning primary or asymptomatic incisional hernia pathology where a therapeutic decision was requested. A consensual attitude was defined by identical care by at least 75% of surgeons. Results: Of the 204 surgeons responding to the study, 44% were under 45 years of age. The therapeutic attitude was consensual in 2 out of 13 clinical cases: surgical abstention was chosen consensually for inguinal hernia in the elderly with comorbidities while surgical treatment was consensually chosen for incisional hernia in a young patient in remission of pancreatic cancer. The under-45s were more likely to undergo surgical repair (5 cases of 13 vs 4 cases of 13, p = 0.03). Conclusion: Although frequent, the management of primary and incisional hernias of the abdominal wall does not reach consensus in the surgical community. Specific recommendations for indications of surgical management or watchful waiting are required. Highlights: There is a great heterogeneity among surgeons in management of asymptomatic abdominal wall pathology, without any consensus. While a surgical indication should be retained in women with a femoral hernia, the consensus threshold has not been reached. The age of the surgeons has an impact on their therapeutic decision, the young surgeons favoring an intervention. The type of care structure does not imply modifications of therapeutic practices of asymptomatic hernias among the surgeons.